Prevalence and predictors of bone health among perinatally HIV-infected adolescents. (15th November 2020) - Mahtab, Sana; Scott, Chris; Asafu-Agyei, Nana Akua A.; Machemedze, Takwanisa; Frigati, Lisa; Myer, Landon; Zar, Heather J.
Abstract : Objectives: Long-term complications of HIV including low bone mineral density remain a concern. We studied the prevalence and predictors of low bone mineral density among South African perinatally HIV-infected adolescents (PHIVA) on antiretroviral therapy (ART). Design: Cross-sectional analysis. Methods: Bone health was evaluated by measuring the calcaneus stiffness index among PHIVA on ART. Low stiffness index was defined as z -score less than −2 SD compared with age-matched and sex-matched HIV-uninfected adolescents (HIV−). Result: Overall, 407 PHIVA (median age: 14 years; 50.4% female; median age at ART initiation: 4.2 years) and 92 HIV− (median age: 13.7 years; 54.4% female) were included. Median duration on ART was 9.8 years (interquartile range 6.8–11.5) with 38% initiating ART at 2 years or less of age. Stiffness index was lower in PHIVA (−0.19 vs. 0.43, P ⩽ 0.001), respectively. During puberty, mean stiffness index increased with Tanner Stage in both PHIVA and HIV− but these increases were larger among HIV−; Tanner Stage II–III (96 vs. 101, P = 0.009) and Tanner Stage IV–V (104 vs. 112, P = 0.001). Among PHIVA, 52 (13%) had low stiffness index. After adjusting for age, sex and Tanner Stage, use of lopinavir/ritonavir [odds ratio (OR) = 2.31, P = 0.012] and viral load more than 50 copies/ml (OR = 2.06, P = 0.023) were associated with increased risk of low stiffness index, while use of efavirenz (OR = 0.41, P = 0.009) was associated with decreased risk of low stiffness index. Conclusion: Stiffness index was a significantly lower in PHIVA than in HIV−, especially during puberty. Among PHIVA, detectable viral load and use of lopinavir/ritonavir were risk factors for low stiffness index. Further longitudinal studies are important to determine the clinical implications. Abstract : Supplemental Digital Content is available in the text